Création de concepts et méthode philosophique chez Gilles Deleuze - Cherniavsky, Axel (2012)
In principle Deleuze's definition of philosophy as a creation of concepts seems to require one to distance oneself from the concept of method. Traditional methods, such as deduction, analysis, intuition appear to be orientated towards a discovery, to knowledge rather than to invention. Furthermore, how could creation obey rules? Nonetheless, the structure of a number of Deleuze's texts suggests that conceptual elaboration does not take place anarchically, but according to a precise procedure. The aim is, firstly, to explicitate this procedure, then to provide the theory of it, since there is no theory of method in the proper sense in Deleuze. To reconstitute it, we will examine the first monographical texts in which Deleuze, in spite of the reservations he expresses at the same period in regard to the notion of method, shows a lively interest in the method of the authors examined.